Morphological study of the anatomical variations of anterior belly of digastric muscle in Brazilian cadavers - Gross, D. J.; Rossi, A. C.; Ferreira-Pileggi, B. C.; Watanabe, L. N.O.; Botacin, P. R. [UNESP]; Prado, F. B.; Freire, A. R. (VM Media Group sp. z o.o, 2023)
Background: Cases of variations in anterior belly of the digastric muscle must be carefully identified to avoid misinterpretations and assist in the correct surgical or aesthetic procedure and help in the teaching of anatomy. The aim of this study was to describe the anatomical variations of anterior belly of digastric muscle in Brazilian cadavers. Materials and methods: Thirty-one human heads were selected, from adult cadavers (18–80 years, 29 males and 2 females). The morphology of the anterior belly of the digastric muscle was observed, identifying the possible anatomical variations that were characterised and classified according to the amount of muscle bellies, fibre direction and place of origin and insertion. The morphometric measurements were performed using a digital calliper. To analyse the data obtained, photographic documentation, anatomical description and individual morphometric description of each muscle belly were performed. The incidence of anatomical variation was obtained in percentage (%). Results: The anatomical variation of the anterior belly of the digastric muscle was present in 6 cadavers (19.31%; 1 female and 5 male). All anatomical variations presented an accessory belly to the anterior belly. However, these accessory bellies were configured differently in the location, direction of muscle fibres and in their dimensions (length and width). Conclusions: The gross anatomy of the anterior belly of the digastric muscle and their variations is important to assist in surgical procedures, pathological or diagnostic function. In addition, asymmetrical variations in the submental region must be carefully identified to avoid misinterpretations. (Folia Morphol 2023; 82, 3: 677–682).
Keywords: anatomical variations; anatomy; digastric muscle; morphology